A whole-body approach for social workers : integrating embodiment and body-mind resources to enhance wellbeing and practice : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University, Palmerston North, New Zealand - Collie, Katrina (Massey University, 2026)
This study explored how embodiment and body–mind resources support social workers’ wellbeing, particularly within contexts marked by high stress and burnout. Motivated by professional experiences and witnessing colleagues navigating similar challenges, the research explored whether embodiment practices could serve as a meaningful form of support. Using an action research methodology that intentionally incorporated embodiment into the research process, the study explored an embodiment program that consisted of four phases: a one-day experiential embodiment workshop, a five-week online extension to support ongoing practice, individual semi-structured interviews and a final phase in which participant insights informed the redevelopment of the embodiment program. Findings indicate that embodied awareness offered diverse support. Embodiment emerged as a practical resource that enhanced wellbeing, professional presence and grounded responsiveness when navigating complex and stressful situations. The collective nature of the program played a key role in supporting learning and integration. However, ongoing organisational pressures and limited structural support hindered the full realisation of the sense of embodiment. Highlighting the need for systemic rather than individualised approaches to wellbeing. The study recommends integrating embodiment within social work education and organisational frameworks to support a shift from self-care toward embodied collective-care, positioning wellbeing as a shared rather than solely personal responsibility. It also highlights the importance of developing a shared definition of embodied awareness to support continuity in future research, policy development and professional practice. Further research is recommended within organisational and educational settings to explore the impact of embodied collective-care on wellbeing, retention and sustainability across diverse groups of social workers.
Keywords: 440901 Clinical social work practice; 350507 Workplace wellbeing and quality of working life